UNRESOLVED ISSUES OF SURGICAL TREATMENT OF GASTROESOPHAGEAL REFLUX DISEASES - I. S. Tarbaev; D. I. Vasilevskii; A. M. Akhmatov (Вестник хирургии имени И.И. Грекова)
The  paper highlights  the  main  issues of  prevalence, pathogenesis  and  diagnosis of  gastroesophageal reflux  disease. The  principles   and  key  problems of  surgical   treatment of  this  pathology are  highlighted.